Gambaran Penggunaan Obat Tradisional Menurut Usada Sebagai Terapi Suportif Pada Penyakit Diabetes Melitus di Kecamatan Selat Kabupaten Karangasem - Ary Pridayanti, Ni Kadek (Bali International Scientific Forum, 2021)
Diabetic Mellitus is a disease characterized by an HbA1c value of 6.5% or higher. The potential enhancement of diabetic mellitus needs to be anticipated by preventive action using traditional medicine. This research aims to know the use of traditional medicine based on Usada as supportive treatment to treat diabetic mellitus disease in Selat sub district Karangasem regency. This research was qualitative explorative research. The data collections were observation and interview of 90 respondents. The result: showed there were 38 kinds of medicinal plants were used by the people in the community. The most used medicinal plant was from garden (58%) with 27 families such as Asteraceae, Cucurbitaceae, and Zingiberaceae (8%) useful for cold (Tis). The most used part of medicinal plant was leaf (39%) which is divided into fresh leaf (95%) and old leaf (79%). Liquid preparation is the most used among the people in the area (71%) with mix ingredients (51%). The most process of medicinal plant was boiled (39%) and the way to consume was drunk (40%). In conclusion: the use of medical plants in Selat sub district were 38 kinds of medical plants especially Asteraceae, Cucurbitaceae, Zingiberaceae families from garden and useful for cold (tis). The most part of medical plant was leaf in fresh and old condition. The process of mix ingredients was boiled and the way to consume was drunk twice a day. Keyword: Diabetic Mellitus, Medicinal plant, Usada